2010
DOI: 10.4028/www.scientific.net/ssp.168-169.533
|View full text |Cite
|
Sign up to set email alerts
|

The Features of TKE and FMR in Nanocomposite-Semiconductor Multilayers

Abstract: Magnetic and magneto-optical properties of multilayers based on the (Co45Fe45Zr10)Z(Al2O3)100-Z composite and amorphous hydrogenated silicon with various thicknesses both of magnetic and semiconductor layers have been investigated. The nonlinear dependence of magnetic and MO characteristics of the nanostructures on the thickness of layers was found. The interface formed on the boundary of two phases (the ferromagnetic granules and the semiconductor ones) strongly influences the magnetic and MO properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…1) that was considerably different from δ(Н) curves found for bulk metal-insulator nanocomposite [6]. The similar pattern was observed for the same chemical composition films, where nanocomposite had been before percolation threshold [1][2][3]. In some cases δ(Н) curves reveal anomalies, such as the TKE sign reversal and the presence of local minimum of the effect in the small fields (Н < 100 Oe).…”
Section: Experimental Details and Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…1) that was considerably different from δ(Н) curves found for bulk metal-insulator nanocomposite [6]. The similar pattern was observed for the same chemical composition films, where nanocomposite had been before percolation threshold [1][2][3]. In some cases δ(Н) curves reveal anomalies, such as the TKE sign reversal and the presence of local minimum of the effect in the small fields (Н < 100 Oe).…”
Section: Experimental Details and Resultssupporting
confidence: 50%
“…Active phase interaction makes difficulties in obtained results interpretation and limits the possibilities of application of the materals mentioned above. Previous studies of multilayer structures (ML) nanocomposites-silicon [(Co 45 Fe 45 Zr 10 ) Z (Al 2 O 3 ) 100-Z (X)/Si(Y)] n [1][2][3], where composite had been before percolation threshold, shown that silicon introduction led to anomalous behavior of electrical, magnetic and magneto-optical properties of ML with small thickness of Si (<2nm). In [3] supposed that TKE spectra and field dependences anomalies related with contributions competition between two composites: (Co 45 Fe 45 Zr 10 )+Al 2 O 3 +Si+Silicides and (Co 45 Fe 45 Zr 10 )+Si+Silicides.…”
Section: Introductionmentioning
confidence: 99%
“…Это удобно сделать в рамках модели Друде-Лоренца. Тогда вклад квазиклассического размерного эффекта в диагональные и недиагональные компоненты ТДП определяется как [12,13]:…”
Section: методы эффективной среды как оптимальные методы моделированиunclassified
“…In the synthesis of film nanostructures of the CoFeB-Si type, silicon enters into chemical reactions with metals to form magnetic and nonmagnetic complexes. As a result, the introduction of even a small amount of silicon led to a significant change in the magnetic and magneto-optical properties up to disappear [1][2][3]. Unfortunately, the number of combinations of compounds that by means of self-organization processes can form a multiphase nanoscale structure and, at the same time, are mutually inert, is limited.…”
Section: Introductionmentioning
confidence: 99%